2019
DOI: 10.1093/rheumatology/kez072
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin Triggered Resolvin D1 reduces inflammation and restores saliva secretion in a Sjögren’s syndrome mouse model

Abstract: Objectives. SS is characterized by chronic inflammation of the salivary glands leading to loss of secretory function, thereby suggesting specialized pro-resolving mediators targeting inflammation to be a viable option for treating SS. Previous studies demonstrated that aspirin-triggered resolvin D1 (AT-RvD1) prevents chronic inflammation and enhances saliva secretion in a SS-like mouse model when applied before disease onset. However, this therapy cannot be used in SS patients given that diagnosis occurs post-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 48 publications
1
28
0
Order By: Relevance
“…As indicated above, our previous studies demonstrated that intravenous treatment with AT‐RvD1 in female NOD/ShiLtJ mice either before or after disease onset reverses SS‐like features 39,41 . Interestingly, in the current study we observed that levels of RvD1 are elevated in both plasma and saliva collected from post‐disease female mice as compared to their pre‐disease counterparts.…”
Section: Resultssupporting
confidence: 77%
See 4 more Smart Citations
“…As indicated above, our previous studies demonstrated that intravenous treatment with AT‐RvD1 in female NOD/ShiLtJ mice either before or after disease onset reverses SS‐like features 39,41 . Interestingly, in the current study we observed that levels of RvD1 are elevated in both plasma and saliva collected from post‐disease female mice as compared to their pre‐disease counterparts.…”
Section: Resultssupporting
confidence: 77%
“…Our previous work demonstrated that systemic treatment with AT‐RvD1 prevents disease onset in the NOD/ShiLtJ mice 39 . Moreover, a similar treatment delivered after disease onset, diminished SS‐like features 41 . Together, these studies indicate a functional role for SPM biosynthesis in SS pathogenesis.…”
Section: Resultsmentioning
confidence: 80%
See 3 more Smart Citations